IMPROVING THE SPEAKING ABILITY OF GRADE SEVEN STUDENTS OF SMPN 1 MEPANGA THROUGH ENGLISH MOVIES - Nopiyanti, Suci; Kamaruddin, Abdul; Zamzam, Fadhilah; Mashuri (FKIP Unismuh Makassar, 2025)
The objective of the study is to find out the effectiveness of the English movie in teaching English speaking to grade seven students of SMPN 1 Mepanga in the academic year 2024/2025. The sample of this pre-experimental research was grading seven students of SMPN 1 Mepanga which consisted of 28 students of the VII D class chosen by using the purposive sampling technique. The data were collected by using a speaking test conducted before and after the treatment, or pre-test and post-test. The data was analyzed by using statistics methods. The result shows that there was a significant improvement in the student’s speaking ability. It was proved by the result of the t-counted (19.13) which was greater than the t-table (1.703) in the significance degree, (0.05). The conclusion of this research indicated that the English movie is effective in teaching English speaking in the classroom and provides a significant effect to improve the students’ speaking ability.